Can One Predict Coronal Mass Ejection Arrival Times With Thirty‐Minute Accuracy? - Gábor Tóth; Bart van derHolst; Ward Manchester IV (Space Weather)
Abstract J. Schmidt and Cairns (2019, https://doi.org/10.48550/arXiv.1905.08961) have recently claimed that they can predict Coronal Mass Ejection (CME) arrival times with an accuracy of 0.9 ± 1.9 hr for four separate events. They also stated that the accuracy gets better with increased grid resolution. Here, we show that combining their results with the Richardson extrapolation (Richardson & Gaunt, 1927, https://doi.org/10.1098/rsta.1927.0008), which is a standard technique in computational fluid dynamics, could predict the CME arrival time with 0.2 ± 0.26 hr accuracy. The CME arrival time errors of this model would lie in a 95% confidence interval [−0.21, 0.61] hr. We also show that the probability of getting these accurate arrival time predictions with a model with a standard deviation exceeding 2 hr is less than 0.1%, indicating that these results cannot be due to random chance. This unprecedented accuracy is about 20 times better than the current state‐of‐the‐art prediction of CME arrival times with an average error of about ±10 hr. Based on our analysis there are only two possibilities: the results shown by J. Schmidt and Cairns (2019, https://doi.org/10.48550/arXiv.1905.08961) were not obtained from reproducible numerical simulations, or their method combined by the Richardson extrapolation is in fact providing CME arrival times with half an hour accuracy. We believe that this latter interpretation is very unlikely to hold true. We also discuss how the peer‐review process apparently failed to even question the validity of the results presented by J. Schmidt and Cairns (2019, https://doi.org/10.48550/arXiv.1905.08961).